2018
DOI: 10.1097/scs.0000000000004602
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Piezosurgery and Hammer-Chisel in Endoscopic Dacryocystorhinostomy

Abstract: Piezosurgery causes shorter operation time, less recurrence, and less pain when compared with hammer-chisel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…In this study, 30% of all patients underwent septum intervention with endonasal DCR; this result is consistent with that in the literature. Considering that septum intervention performed during surgery facilitates the EE-DCR procedure, it may have a negative effect on the functional success (17) . In this study, in the first set of cases, the need for septoplasty was more, and it decreased with increasing level of experience.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, 30% of all patients underwent septum intervention with endonasal DCR; this result is consistent with that in the literature. Considering that septum intervention performed during surgery facilitates the EE-DCR procedure, it may have a negative effect on the functional success (17) . In this study, in the first set of cases, the need for septoplasty was more, and it decreased with increasing level of experience.…”
Section: Discussionmentioning
confidence: 99%
“…In 1989, McDonough and Meiring described the first modern endoscopic endonasal DCR procedure. Since then, instruments, visualization, and surgical techniques have evolved to improve endoscopic endonasal DCR (EDCR) [ 3 6 ], which has emerged as a standard method over the past decade. Moreover, the surgical success rates of EDCRs and external DCRs are now equivalent, according to the findings of several studies, and with better cosmetic results reported for EDCR [ 7 9 ].…”
Section: Introductionmentioning
confidence: 99%